Outcome of distal femoral replacement: Influence of trauma vs. elective indications – A prospective single-center study - Anne Elisabeth Postler; Franziska Beyer; Cornelia Lützner; Jörg Lützner (PLoS ONE, 2026)
Background Distal femoral replacement (DFR) is often the last leg-saving option in advanced femoral bone defects after total knee arthroplasty (TKA) and periprosthetic distal femoral fractures. The aim of this study was to compare the midterm outcome of DFR following periprosthetic fracture or elective TKA revision. Methods This prospective cohort study included 93 DFR patients (49 trauma, 44 elective) from 2010 to 2021. DFR for revision in periprosthetic joint infection (PJI) or tumor resections were not included. Data on demographics, surgical history and reason of failure until DFR, revision rates, satisfaction and pain in mean 5 years postoperatively were collected. Revision incidence was estimated using cumulative incidence functions accounting for death as a competing event, while patient mortality was analysed using Kaplan-Meier estimation. Multivariate Cox regression models were used to assess which parameters were associated with DFR revision. Results Trauma patients had in mean 1.5 (SD 0.9) prior surgeries, while elective patients had 3.1 (SD 1.5), p < 0.001. Satisfaction was higher after trauma (6.9/10) compared to elective DFR (5.4/10). The 1- and 5-year cumulative incidence of revision was 4.1% and 13.9% in trauma patients and 7.0% and 42.0% in elective patients, respectively. The 1- and 5-years mortality rates were 18.7% and 47.5% (trauma) and 6.9% and 16.8% (elective). Female sex was associated with lower, previous constraint TKA, and elective indication were associated with higher revision risk. Conclusion There were higher revision rates but lower mortality in elective DFR compared to trauma patients, mainly caused by pre-existing conditions. Surgeons should take this into consideration during shared decision making for DFR. Registry and the registration number of the study German Clinical Trial Register (DRKS). DRKS-ID: DRKS00036378.